The hexosamine biosynthetic pathway induces gene promoter activity of the cardiac-enriched isoform of acetyl-CoA carboxylase - Imbriolo, Jamie (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.